Pulmonary metastasectomy in pediatric patients. Issue 1 (December 2015) - Erginel, Basak; Gun Soysal, Feryal; Keskin, Erbug; Kebudi, Rejin; Celik, Alaaddin; Salman, Tansu
Abstract Background This study aims to evaluate the outcomes of pulmonary metastasectomy resections in pediatric patients. Methods We retrospectively reviewed the medical records of 43 children who were operated on in the Pediatric Surgery Clinic between January 1988 and 2014. Forty-three children (26 boys; 17 girls; mean age 10 ± 4.24 years, range 6 months–18 years) who underwent pulmonary metastasectomy resection were included in the study. The patients were evaluated based on age, gender, history of disease, surgical procedures, complications, duration of hospitalization, duration of chest tube placement, and procedure outcome. Results Indications for pediatric resections were oncological. Metastasis was secondary to Wilms' tumor in 14 patients, osteosarcoma in 7 patients, Ewing's sarcoma in 5 patients, rhabdomyosarcoma in 5 patients, lymphoma in 3 patients, hepatoblastoma in 2 patients, and other tumors in 7 patients. A total of 59 thoracotomies were performed. Approaches utilized included unilateral posterolateral thoracotomy (n  = 33), bilateral posterolateral thoracotomy (n  = 8), and sternotomy (n  = 2). Wedge resection was the procedure of choice (n  = 44). In selected cases, 11 segmentectomies, 3 lobectomies, and 1 pneumonectomy were performed. There was no perioperative mortality. One patient suffered prolonged air leak and three patients from fever. All patients received chemotherapy. Radiotherapy was administered to 16 patients (37.2 %). Of those 16 patients, 7 had Wilms' tumor, 6 had Ewing's sarcoma/PNET, and 3 were rhabdomyosarcoma patients. During a median follow-up of 3 years, the overall survival was 74.4 %. Conclusions Multidisciplinary treatment involving pediatric oncologists, surgeons, and radiation oncologists is necessary to obtain positive results in children who have pulmonary metastases of oncological diseases. Wedge resection is a suitable option for children because less lung tissue is resected.